The Structuring of the Lands Nature Reserve Fund Central Forest-Steppe of Ukraine - Halchenko, Nadiya; Ilchenko, Volodymyr; Mudrak, Oleksandr; Mudrak, Galyna (International Journal of Engineering and Technology, 2018)
In the work for the territory of the Central Forest-steppe (Vinnitsa, Cherkasy and Poltava regions), the structure of the lands of the nature reserve fund (NRF) was carried out. The current analysis of the state of lands of the NRF and the definition of priority tasks for its development is important for the ecological stability of the territory of the regions. The given structuring of lands of the NRF consists in the quantitative distribution of administrative regions. The grouping of object categories by area and number and the establishment of a reserve level for the regions is done. The results show that a number of disproportions and problems of nature use are distinguished on the lands of the NRF of the region. In particular, the strictly uneven is the protection of administrative districts, the differences between which reaches dozens of times.